Structural performance of light wood shear walls built with insulated sheathing panels. (15th August 2021) - Spasojevic, Marko; Daneshvar, Hossein; Niederwestberg, Jan; Chen, Yuxiang; Hei Chui, Ying; Gong, Meng
Highlights: Intermediate insulation reduces the lateral resistance of light wood-frame shear wall. Intermediate insulation reduces the stiffness of light wood-frame shear wall. Lateral strength of a wall can be predicted based on the strength of its nailed joint. Abstract: Placing an insulation layer between sheathing and lumber framing members reduces thermal bridging in light wood-frame wall construction. However, this soft intermediate insulation layer compromises the lateral resistance and stiffness of the wall due to its relatively low mechanical properties. An experimental study on full-scale shear walls was conducted to investigate the influence of intermediate insulation on the lateral resistance and deflection of light wood-frame walls. Finite element analysis was used for all test specimens and the results were compared to the test data and responses predicted using the mechanics-based design equations provided by the Canadian timber design standard. Results show that an intermediate insulation layer has a significant impact on the lateral resistance and stiffness of light wood-frame walls. Furthermore, it was shown that the lateral strength of such wall assemblages can be predicted with sufficient accuracy based on the strength of its nailed joints using the code simplified design equation, provided that the insulation thickness is not greater than 51 mm. It was also noted that the predicted load-displacement responses using the equation from the Canadian timber design standard are comparable to the predicted responses obtained from the finite element analysis.